Information and Communication Technologies Acceptance Models in Universities - Chancusing, Juan Carlos (2019)
TAM (Technology Acceptance Model) is used in Computational Science research to collect user feedback for Information Systems (IS). Carrying out this research it was found that the TAM is one of the most significant methodological individualist approaches related to adoption of Information and Communication Technologies (ICT). Different modifications have been incorporated into this model. A systematic review method was used in order to identify studies related to intention to use a technology in universities. 61 primary studies were selected from the different scientific databases. The results show that TAM has been applied in studies related to adoption of e-learning, web 2.0 and ICT. Although TAM has proven to be a coherent model, it still has limitations that can be perceived by other intellectuals as opportunities for future research.